Frontiers, insurgencies and counter-insurgencies in South Asia, 1820-2013 - Roy, Kaushik, 1971- author.
1 online resource (xix, 226 pages)
Keywords: This book uses cross-cultural analysis across Eurasia and Afro-Asia to trace the roots of contemporary border disputes and insurgencies in South Asia. It discusses the way frontiers of British India, and consequently the modern states of India and Pakistan, were drafted through negotiations backed up by organized violence, showing how this concept found its fruition in present-day counter-insurgency measures.--Provided by publisher.